Strategi Pembelajaran Guru Tāḥfiẓh dalam Peningkatan Hafalan dan Pembentukan Karakter Religius Siswa - Alifa, Alifia Zuhriatul; Asrori, Mohammad; Mulyono, Mulyono (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2025)
This study explores the influence of two teaching methods in the Al-Qur'an memorization program at SMAN 1 Ngimbang Lamongan, namely the sorogan and musyafahah methods, and their impact on the accuracy and speed of students' memorization. The background of this study is based on the importance of effective teaching of Al-Qur'an memorization in the context of religious education in Indonesia, where the method used can affect students' success in memorizing. Previous studies have shown the effectiveness of the sorogan method, but few have examined the contribution of the more interactive musyafahah method. The research method used is a qualitative case study approach with observation and in-depth interview techniques. Data were collected from students who participated in the Al-Qur'an memorization program using both methods. Data analysis was carried out thematically to assess the differences in the effectiveness of the two methods in improving the accuracy and speed of memorization. The results showed that the musyafahah method, with direct interaction between students, teachers, and classmates, had a more significant impact on accelerating the memorization process and improving the accuracy of students' memorization compared to the sorogan method. These findings emphasize the importance of active involvement in learning, which is in line with constructivist learning theory. However, challenges related to time constraints and varying student motivation were also found to be major obstacles to the success of the memorization program. The implications of this study suggest that a combination of both teaching methods, with an emphasis on social interaction, can optimize the memorization process. This study is expected to contribute to the development of more effective and relevant Qur'an memorization teaching methods in the context of education in Indonesia. In conclusion, this study suggests further research with larger and more diverse samples to deepen the understanding of the factors that influence students' memorization success.